IMPLEMENTASI EKSTRAKURIKULER PANAHAN DALAM MENGEMBANGKAN KETERAMPILAN MOTORIK KASAR PESERTA DIDIK KELAS VI DI SD JUARA AL-HIKMAH JAYAPURA - Tasya Fajrianti, Dinda; Rofiki, A. Arif; Wahyu Nengsih, Luluk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the importance of developing elementary school students’ gross motor skills through structured activities that are appropriate to their physical developmental needs. One activity that can support such development is archery as an extracurricular activity, as it trains body balance, coordination, and movement control. This study aims to describe the implementation of archery extracurricular activities in developing the gross motor skills of sixth-grade students at SD Juara Al-Hikmah Jayapura. This study employed a qualitative approach with a descriptive research design. Data were collected through observations, semi-structured interviews, and documentation, and were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that the implementation of the archery extracurricular activity was carried out well through the stages of planning, implementation, and evaluation. Planning involved preparing the training schedule, determining the objectives and materials, and preparing the necessary facilities and equipment. The activities were conducted in a structured manner through prayer, warm-up exercises, basic archery technique training, archery practice, direct guidance, and closing activities. Evaluation was conducted throughout the training process and at the end of the activities through observation and feedback on students’ techniques. Furthermore, the archery extracurricular activity contributed to the development of students’ gross motor skills, as indicated by improvements in their ability to maintain body balance, coordinate eye-hand movements, and control movements when drawing, aiming, and releasing the arrow. The activities were conducted gradually and systematically, while also providing learning experiences that supported students’ accuracy, concentration, discipline, and self-confidence during training. Therefore, archery extracurricular activities can serve as an effective activity to support the development of gross motor skills among sixth-grade students at SD Juara Al-Hikmah Jayapura.